Adaptation of Islamic Law in the Dutch Colonial Era: Fiqh al-aqalliyyāt, Maqasid Al-Shariah, and Its Legacy for Modern Indonesian Islamic Legal Institutions - Zaini, Ahmad; Ridho, M. Zainor; Muttaqin, E. Zaenal; Yussof, Hilmy Baihaqy (IAIN Manado, 2025)
This study examines the dynamics of Islamic jurisprudence (Fiqh al-aqalliyyāt) during the Dutch colonial period in Indonesia, with a focus on the role of Maqasid al-Shariah (Islamic principles) in guiding the adaptation of Islamic law amidst the dominance of colonial law. In a situation where Muslims were in a minority position politically and in power, Islamic law underwent a process of negotiation and adjustment, both through religious court institutions and social-religious practices in society. This study employs a historical-comparative approach to examine the interaction between Islamic law and colonial law, and to investigate its long-term implications for the structure and functioning of contemporary Islamic legal institutions in Indonesia. The results show that the adaptation of Islamic law in the colonial era was driven not only by the need to maintain the identity and continuity of sharia but also by considerations of benefit in line with the principles of Maqasid al-Shariah. This historical legacy has had a profound influence on the modern Islamic legal framework, both in its institutional aspects and in the legal substance that remains applicable to this day.